ON WAYS TO BUILD IMMUNITY AGAINST HYBRID WARFARE IN CADETS THROUGH TEACHING HIGHER MATHEMATICS - Rakhmanov Istam Yarikulovich (European Science Publishing, 2024)
This article discusses the issue of forming intellectual immunity against hybrid wars and cadets against such wars as an example of teaching higher mathematics.
Keywords: Hybrid warfare, bacteria, bacteriological weapons, nuclear weapons, explosives, higher mathematics, function, exponent, differential equation, intellectual immunity, practical skills.